Consuming Rural Territories through Food – A Segmentation Analysis Based on the Food Choices of Urban Specialty Stores' Customers. Issue 8 (22nd November 2022) - Figueiredo, Elisabete; Forte, Teresa; Eusébio, Celeste; Silva, Alexandre; Truninger, Mónica
ABSTRACT: The increasing interest of consumers in rural provenance food products is known to meet concerns regarding authenticity, health, safety, and sustainability and to be based on knowledge and familiarity. Based on the results of a survey to 1553 customers of 24 urban specialty shops, located in three Portuguese cities, this study aims at identifying different segments of consumers of rural provenance foods according to the criteria they value when acquiring and consuming those products. From a hierarchical cluster analysis based on shopping preferences, three clusters were identified: The Influenced, choosing the products mainly by recommendation; The Provenance Seekers, privileging provenance and related qualities; and The All-embracers, considering a multiplicity of criteria when shopping. These clusters differ in terms of socio-demographic profiles, products bought, consumption behavior, familiarity with rural areas, and images of food products and territories of provenance. Results show the mutual influence of these dimensions on food preferences.